Daughter of the empire - Feist, Raymond E. (Bantam Books, 1988)
Mara, a young, untested Ruling Lady of Kelewan, is called upon to lead her people in a heroic struggle for survival. But first she must rally an army of rebel warriors, form a pact with the alien cho-ja and marry the son of a hated enemy. Queen Mara of Acoma vows to avenge the deaths of her brother and father, even if it means killing her own husband.